The effect of manipulating task constraints on game performance in youth field hockey manipulating task constraints - Timmerman, E. A.; Farrow, D.; Savelsbergh, G. J. P. (International Journal of Sports Science & Coaching, 2017)
The purpose of this study was to examine the influence of manipulating game constraints on match performance in youth field hockey. A total of 25 participants aged 10.6-14.6 years old played four different 25-min games where density (228m² or 158m² per player) and/or number of players (11 per side or 8 per side) was manipulated. Match performance was determined by using notational analysis and physical demands were determined by using GPS analyses. Manipulating the number of players led to an increase in a successful passes (+2.68 passes), skilled actions (+3.73 skilled actions) and successful actions (+3.77 successful actions) performed per player and also created a more advantageous environment to enhance decision making. Increasing the density led to a decrease in unsuccessful dribbles (-0.59 unsuccessful dribbles) made by players and an increase in high intensity running (+38m) and sprinting (+21.2m). The findings of this study provide an insight into the effect of manipulating task constraints in skilled junior field hockey and the findings highlight that all types of constraints influence emergent performance in their unique way and that coaches should consider these interactions to promote specific playing behaviour. ABSTRACT FROM AUTHOR